INTERNALISASI ADAB ISLAMI BERBASIS BUDAYA ACEH DALAM PEMBENTUKAN KARAKTER SOSIAL SISWA SEKOLAH DASAR - Udrikal Muna; Rahmad Syah Putra; Bansu Irianto Ansari; Fatia Nurahmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Character education at the elementary school level plays a strategic role in shaping students’ social attitudes and behaviors from an early age. In the context of Aceh, character education cannot be separated from the internalization of Islamic adab integrated with local culture. This study aims to analyze the internalization of Islamic adab based on Acehnese culture in the formation of elementary school students’ social character. This research employs a qualitative approach with a literature study design by analyzing various scholarly journal articles, research findings, and policy documents relevant to Islamic character education, Acehnese culture, and elementary education. The results indicate that the internalization of Islamic adab based on Acehnese culture is implemented through the integration of Islamic moral values into the curriculum, the habituation of Islamic school culture, teachers’ role modeling, and the utilization of Acehnese local wisdom such as narit maja as a medium for moral value inculcation. This internalization process contributes positively to the development of students’ social character, including politeness, social care, cooperation, and responsibility. However, the implementation of character education still faces challenges, such as variations in teachers’ competencies, limited learning resources based on local culture, and a lack of consistency in value application within the family environment. This study concludes that the internalization of Islamic adab based on Acehnese culture is a relevant and effective approach to shaping elementary school students’ social character and requires reinforcement through collaboration among schools, families, and communities to ensure sustainability.